An Analysis of Grammatical Equivalence Used by Students in Translating News Item Text - Irawan, Bambang; Erviana, Ridha Ikhva (English Education:Journal of English Teaching and Research, 2024)
ABSTRACT Spreading news in this era seems to be easier due to the rapid development of technology. However, some readers from different language background seem to have difficulties in understanding the news because of language barrier. Translation is needed to overcome this problem and to make news understandable for readers in greater community. This research examined the types of grammatical equivalence used by the students in translating news item text from Indonesian to English. Besides, this research also aimed to figure out the problems found in the students’ grammatical equivalence. Descriptive qualitative approach was used in this research since the data were presented in the form of description instead of number. The primary data were taken from news item text translation works done by the seventh-semester students of English Department of Pamulang University in academic year of 2022/2023. The data were collected using Google Form and then analysed using the grammatical equivalence theory proposed by Baker (2001). There were five steps of data analysis used in this research: observing the data, identifying the data, classifying the data, and evaluating the data. The results showed that the students used five types of grammatical equivalence namely number, gender, person, tenses & aspects, and voice. The results also revealed that the students faced problems related to number and tenses & aspects.